Enhancing Cognitive Independence and Creativity in Higher Education Through Neuroeducation: An Empirical Study - Volkotrubova, Albina; Liu, Jie; Andrusenko, Oleksandr; Provorova, Yevheniia; Vnukova, Оlga (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: The research aims to empirically examine the effectiveness of integrating neuroeducation into higher education by analyzing how an integrated neurodidactic model enhances students’ cognitive independence and creativity within technology-enhanced learning environments. Methodology: The methodological underpinning was the system-activity approach. A quasi-experimental pre-test/post-test control group design was employed to assess the effectiveness of the neurodidactic intervention.Among the employed methodologies were questionnaires utilizing the MSLQ scale, creativity assessments developed by D. Johnson, S. Mednick, and E. Torrance, the expert evaluation method, as well as statistical analysis, including the Mann–Whitney U-test and Spearman’s coefficient. Main Findings: A total of 294 students participated in the pedagogical experiment, with 147 assigned to the control group and 147 to the experimental group. The findings revealed that the expert assessment of creativity in the experimental group (EG) averaged 26.32 points, compared to 22.60 points in the control group (CG); regarding the motivational criterion, the EG scored 4.1, while the CG scored 3.4. A marked enhancement in the measures of independence and creativity was observed within the experimental group. These improvements were statistically significant and confirmed the effectiveness of the neurodidactic intervention compared with traditional instruction. Novelty/Originality of this study: The scientific novelty of the study lies in the empirical validation of an integrated neurodidactic model that systematically combines multiple cognitively grounded strategies within higher education. Unlike previous studies focusing on isolated neuroeducational techniques, this research demonstrates simultaneous improvements in cognitive independence and creativity through a technology-enhanced learning framework.